PERILAKU MENYONTEK MAHASISWA MUSLIM - Warsiyah Warsiyah (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
This study aimed to examine the effect of the direct and indirect simultaneously in a model pathway analysis. More specifically, this research examines (1) the effect of rate on Faith and Academic Procrastination Attitudes toward Cheating, (2) the direct or indirect effect of Level of Faith, Academic Procrastination and Attitudes toward Cheating on Cheating Behavior. Hypothesis testing was conducted based on data collected by questionnaire, which was composed specifically for this study, of 192 Muslim students studying in the Faculty of MT Walisongo IAIN Semarang, selected clusters. Hypothesis testing is done by using path analysis or path analysis. The results of path analysis showed empirically Faith rate has a direct negative effect while empirically Academic Procrastination has a significant positive direct effect on Attitude toward Cheating. However, the level of faith and Academic Procrastination and statistically or practically no direct influence on the attitude towards Cheating. Variable Level of Faith and Academic Procrastination indirectly (through attitude toward cheating) has a significant influence on Cheating Behavior. While the variable Attitude toward Cheating does not have a direct or indirect effect on Cheating Behavior.Keywords: Behavior cheat, attitudes toward cheating, academic procrastination, the level of faith.